UV-Vis-IR spectroscopy on VO₂ thin film near the metal-semiconductor transition - Thanat Kaewsuksri (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
Vanadium dioxide (VO₂) undergoes a phase transition near the room temperature at 68 °C. This transition results in abrupt changes in electrical conductivity and optical property (especially reflectance and transmittance in the infrared region), which can be useful in many applications of sensing and switching. However, there are very few studies focus on optical property of VO₂ near the transition temperature. This project studied optical reflection of VO₂ covering UV, visible light, and IR region at various temperatures (from 25 °C to 100 °C) which is necessary to understand the fundamental properties and the way to improve VO2 thin film for optical devices. The temperature dependent resistance measurement shows that the VO2 thin film has a transition at 73 ± 5 °C. The temperature dependent reflectance of VO₂ thin film was observed in region of 200 - 900 nm. At the phase transition, the change in reflection is obviously observed in region of 300 - 400 nm and 700 - 900 nm which result in the transition temperature in range of 65.5 °C - 68.4 °C and 64.9 °C - 68.4 °C, respectively. The transition temperatures extracted by optical method is less than those retrieved from electrical method. It is most likely due to the photoexcitation.